A Comparative Study of Punjab and Xinjiang: Muslim Education in Modern Times (1857-1947) - Dandan, Ma (Annals of Human and Social Sciences, 2022)
Education is an important aspect of national development and people's livelihood, and its development will be restricted by political, economic, historical and other factors. In modern history, both China and Pakistan have made active explorations and attempts in the process of realizing national cultural rejuvenation through educational innovation. Xinjiang and Punjab are important node cities in the "Belt and Road" exchanges between China and Pakistan. They are similar in geography, ethnic structure, natural endowments and customs, and have both experienced the process of transformation from traditional Islamic education to modern education. Historical comparison method, on the basis of extensive literature reading, to sort out the process of Islamic education modernization in Punjab and Xinjiang Province under the influence of colonial rule in the mid-19th century and mid-20th century. Summing up the similarities and differences of their development, we hope to find out the development laws of modern education in the two countries, and lay a research foundation for the comparative study of education between China and Pakistan in the future.